A fusion ORF3a-E subgenomic RNA involved in SARS-CoV-2 infection efficacy by influencing cellular protein synthesis - Zhang, Yifan; Li, Jing; Zhang, Xinglong; Zhang, Xin; Li, Jiali; Li, Heng; Zhao, Xin; Zhang, Zihan; Li, Yingyan; Chen, Keqi; Peng, Shasha; Shi, Haijing; et al. (Frontiers in Immunology, 2025)
Subgenomic RNAs (sgRNAs) are discontinuous transcription products of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that are involved in viral gene expression and replication, but their exact functions are still being studied. Here, we report the identification of a nested ORF3a-sgRNA, the fusion ORF3a-E-sgRNA, which is involved in the infection process of SARS-CoV-2. This sgRNA encodes both ORF3a and E and can be detected throughout the viral life cycle in SARS-CoV-2-infected cells with high copy numbers. ORF3a-E-sgmRNA guides ORF3a translation and promotes the expression of cellular ribosomal protein S3 (RPS3), increasing translation levels. Single-cell sequencing of a SARS-CoV-2-infected human bronchial epithelial cell line (16HBE) revealed that maintenance of this stable translational environment by ORF3a-E-sgmRNA is important for SARS-CoV-2 assembly and release capabilities and is also beneficial for viral evasion of host innate immunity. More importantly, the transcription level of ORF3a-E-sgRNA may contribute to differences in infection processes between the Wuhan strain and the XBB strain of SARS-CoV-2.